The Use of Aids in TEFL (Teaching English as a Foreign Language): A Case Study at the MTs SA Al-Istiqomah in Ciheulang, Cianjur, West Java, Indonesia - Helmie, Jauhar (ATIKAN, 2014)
ABSTRACT: In Indonesia, the Ministry of Education and Culture has been decided that English becomes one of the first foreign languages taught in various levels. It is taught at school as compulsory subject in both Junior High School level and Senior High School level. In order to make the teachers teach well, proper, and the students feel interested in learning the subject, he or she should apply teaching aids. This paper has related to the use of aids in teaching English in Junior High School, there are students of MTs SA (âMadrasah Tsanawiyah Sekolah Agamaâ or Junior High School for Islamic Religion) Al-Istiqomah in Ciheulang, Cianjur, West Java, Indonesia, at the 1st A grade, 1st B grade, and 2nd grade, female and male. The research method that the writer uses for this report are descriptive, comparative, questioners, and library research. The problem over this paper consists of the importance of using aids in teaching English. Based on the analysis, it shows that the use of aids in teaching English make the students interest to studying English and can lose their boredom. So that, teachers can teach the students to be more interest to study English than before with using aids.KEY WORD: Teaching-learning process, teaching techniques, media, studentsâ ability, audio, visual aids, teachers, and interesting to study English.IKHTISAR: âPenggunaan Alat Bantu dalam PBIBA (Pengajaran Bahasa Inggris sebagai Bahasa Asing): Studi Kasus di MTs SA Al-Istiqomah di Ciheulang, Cianjur, Jawa Barat, Indonesiaâ. Di Indonesia, Kementerian Pendidikan dan Kebudayaan telah memutuskan bahwa bahasa Inggris menjadi salah satu bahasa asing pertama yang diajarkan di berbagai tingkatan. Ianya wajib diajarkan di sekolah, baik di tingkat SMP (Sekolah Menengah Pertama) maupun SMA (Sekolah Menengah Atas). Agar guru mampu mengajar dengan baik, tepat, dan siswa merasa tertarik untuk belajar, guru harus menggunakan alat-alat bantu. Makalah ini berkenaan dengan penggunaan alat bantu dalam mengajar bahasa Inggris di SMP, yakni para siswa MTs SA (Madrasah Tsanawiyah Sekolah Agama) Al-Istiqomah di Ciheulang, Cianjur, Jawa Barat, Indonesia, pada Kelas I-A, I-B, dan Kelas 2, perempuan dan laki-laki. Metode penelitian yang penulis gunakan adalah deskriptif, komparatif, kuesioner, dan studi pustaka. Masalah dalam makalah ini adalah pentingnya menggunakan alat bantu dalam mengajar bahasa Inggris. Berdasarkan hasil analisis menunjukkan bahwa penggunaan alat bantu dalam mengajar bahasa Inggris membuat para siswa tertarik untuk belajar bahasa Inggris dan bisa menghilangkan kebosanan mereka. Sehingga, para guru dapat mengajar para siswa agar menjadi lebih menarik untuk belajar bahasa Inggris, daripada sebelumnya, dengan menggunakan alat bantu.KATA KUNCI: Proses belajar-mengajar, teknik mengajar, media, kemampuan siswa, audio, alat peraga, guru, dan menarik untuk belajar bahasa Inggris.About the Author: Jauhar Helmie, M.Hum. is a Lecturer at the Department of English Education FKIP UNSUR (Faculty of Education and Teacher Training, Suryakancana University) in Cianjur, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail: jauhar_3rd@yahoo.co.idHow to cite this article? Helmie, Jauhar. (2014). âThe Use of Aids in TEFL (Teaching English as a Foreign Language): A Case Study at the MTs SA Al-Istiqomah in Ciheulang, Cianjur, West Java, Indonesiaâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.4(2) December, pp.201-206. Bandung, Indonesia: Minda Masagi Press, FKIP UNSUR Cianjur, and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (December 1, 2014); Revised (December 8, 2014); and Published (December 27, 2014).